The main modern theoretical aspects of the relationship between the economic potential and the economic power of the state - Semenenko, Oleh; Onofriichuk, Petro; Vodchyts, Oleksandr; Taran, Olha; Cherevatyi, Taras; Romanchenko, Olha (Social Development and Security, 2022)
Purpose: is the disclosure of the main modern theoretical aspects and features in the relationship of the dialectical concepts of the economic potential and economic power of the state within the framework of today. Design/Method/Approach: the main methods of research are dialectical methods, analysis and synthesis of economic processes, methods of economic theory, methods of economic logic. Findings: the essence and content of the concepts of economic potential and economic power of the state are revealed, theoretical views on their relationship with each other are defined, possible ways of increasing the effectiveness of increasing the economic potential and economic power of the state are revealed. Theoretical implications: the main results of the research on the topic of the article are: the disclosure of the main modern aspects of the relationship between the economic potential and the economic power of the state, their structural elements are revealed and the dependence formed between them, as well as the views on further research of the issues covered in the article are defined. Paper type: descriptive, theoretical, dialectical.